Pengaruh Literasi Keuangan, Motivasi, dan Percaya Diri terhadap Keputusan Investasi bagi Mahasiswa - Amalia Nur Chasanah; Masitha Fahmi Wardani; Marlyen Honestya Safeta (Eksos, 2022)
Communities allocate the money they have into consumption, savings and investment. Investment is one way of allocating finances for future profits. Making this investment is a way for someone to learn independently in allocating their finances. Investment decisions are influenced by various factors. This research will look at the effect of financial literacy, motivation and self confidence on investment decisions in college students. The sampling criteria is university student in Semarang and have investment in the form of savings, gold or something else. The number of respondents studied was 109 students. Data processing using SEM PLS. The results obtained are financial literacy and self confidence have a positive and significant effect, but the motivational variable has no significant effect.